2005
DOI: 10.1038/sj.mp.4001666
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genome scan and Ordered-Subsets Analysis of autism endophenotypes support language QTLs

Abstract: Autism is a neurodevelopmental syndrome with early childhood onset and deficits in three behavioral and cognitive dimensions: language, social skills and repetitive or restrictive behaviors. We hypothesized that using these endophenotypes would provide more power to detect linkage than the diagnosis of autism. Previously, we reported results for a nonparametric quantitative trait locus (QTL) genome scan in 152 families with autism, which revealed a linkage peak related to spoken language on 7q35. Here, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 41 publications
3
84
0
2
Order By: Relevance
“…53 We did not find significant supporting evidence for language-related signals on other chromosomes (2, 3, 7q (B103 cM) or 13) that were identified in previous linkage studies. 13,29,30 In comparing our results to other studies, we provide strong support for a chromosome 7 autism locus, and lesser but still compelling support for loci on chromosomes 3, 4 and 11. However, we were not able to reproduce a number of substantial signals reported by others.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…53 We did not find significant supporting evidence for language-related signals on other chromosomes (2, 3, 7q (B103 cM) or 13) that were identified in previous linkage studies. 13,29,30 In comparing our results to other studies, we provide strong support for a chromosome 7 autism locus, and lesser but still compelling support for loci on chromosomes 3, 4 and 11. However, we were not able to reproduce a number of substantial signals reported by others.…”
Section: Discussionsupporting
confidence: 75%
“…Based on recent findings by others, we also conducted secondary stratified and quantitative trait analyses of: (1) families with only male affected children (male-only, MO) versus families where there was at least one affected female child (female-containing, FC); 17,20 (2) families with or without developmental regression; 27 and (3) age at first word and phrase as quantitative traits. 13,[28][29][30] Our results provide strong evidence for an autism locus on chromosome 7q with the evidence for linkage being strongest in the subset with the strictest diagnosis. This provides strong confirmation of previous results for chromosome 7q.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…40,[119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] Research groups, study design and main findings of linkage studies that reported positive results are summarized in Table 1 for genome-wide linkage and association studies with a qualitative AD phenotype, and in Table 2 for linkage studies with either a quantitative phenotype, a specific qualitative endophenotype, or other specific linkage models. 122,123,127,130,[138][139][140][141][142][143][144][145][146][147][148] From Table 1, it can be seen that linkage has been found in at least two independent studies in regions 2q, 3q25-27, 3p25, 6q14-21, 7q31-36 and 17q11-21.…”
Section: Linkage Studiesmentioning
confidence: 98%